BS EN ISO 21872-1 AMD1. Microbiology of the food chain. Horizontal method for the determination of Vibrio spp. Part 1. Detection of potentially enteropathogenic Vibrio parahaemolyticus, Vibrio cholerae and Vibrio vulnificus (27th July 2021) - British Standards Institution,
No abstract available